Collision Thyroid Tumours: Papillary And Follicular Carcinoma A Rare Collision - Kamran Zamurrad Malik; Muhammad Zubair; Junaid Akram; Tehreem Ramzan Malik; Aaminah Hanif (Pakistan Armed Forces Medical Journal, 2026)
Collision tumours are very rare and comprise components of varied behavior, treatments, and prognosis. The coexistence of histologically different malignancies in thyroid gland poses a diagnostic and therapeutic challenge in the absence of clearly defined guidelines. We present a case of collision thyroid tumor with co-occurrence of Papillary and Follicular thyroid carcinomas where Follicular thyroid carcinoma was diagnosed on histopathology following lobectomy whereas Papillary carcinoma was diagnosed in the other lobe after completion thyroidectomy.